Time alignment in speech and speaker recognition - Lipeika, Antanas; Lipeikienė, Joana (Lietuvos matematikos rinkinys, 2001)
Time scale alignment problems in speech and speaker recognition by voice are investigated. Dynamic programming approach to solution of this problem is discussed.